COVID-19 challenges to access to education for learners living with severe disabilities: An education law perspective - Johan Beckmann; Mariëtte Reyneke (Perspectives in Education, 2021)
Thro (2005:1) points out that the Supreme Court of the United States has recognised that “education is perhaps the most important function of state and local governments" because "it is doubtful that any child may reasonably be expected to succeed in life if he is denied the opportunity of an education”. He adds that the Court has stressed “the importance of education in maintaining our basic institutions …”